The effect of the supra-cognitive learning cycle strategy on the reflective thinking of the fifth literary grade students (Journal of the College of Basic Education, 2022)
The current research aims to identify (the effect of the meta-cognitive learning cycle strategy on the reflective thinking of the fifth literary grade students).To achieve the aim of the research, the researcher formulated the following two zero hypotheses:- There is no statistically significant difference at the level of significance (0.05) between the mean scores of students in reflective thinking according to the (supra-cognitive learning cycle strategy), and the mean scores of students in reflective thinking that studied the same subject according to the usual (standard) method.